2019
DOI: 10.1016/j.nmd.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber dysfunction contributes to weakness in inclusion body myositis

Abstract: Atrophy and fatty infiltration are important causes of muscle weakness in inclusion body myositis (IBM). Muscle weakness can also be caused by reduced specific force; i.e. the amount of force generated per unit of residual muscle tissue. This study investigates in vivo specific force of the quadriceps and ex vivo specific force of single muscle fibers in patients with IBM. We included 8 participants with IBM and 12 healthy controls, who all underwent quantitative muscle testing, quantitative MRI of the quadric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The molecular changes underlying muscle weakness remain unclear in IMNM. Lassche et.al conducted an experiment on contractile function in IBM and found that the reduced formation of attached actin-myosin cross-bridges may lead to muscle ber weakness [19]. A study on nemaline myopathy with de nite mutations also revealed impaired actin-myosin interaction causing decreased muscle ber force [20].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular changes underlying muscle weakness remain unclear in IMNM. Lassche et.al conducted an experiment on contractile function in IBM and found that the reduced formation of attached actin-myosin cross-bridges may lead to muscle ber weakness [19]. A study on nemaline myopathy with de nite mutations also revealed impaired actin-myosin interaction causing decreased muscle ber force [20].…”
Section: Discussionmentioning
confidence: 99%
“…30 Single muscle fiber calcium sensitivity of force was intact in muscle biopsies from patients with inclusion body myositis, an acquired muscle disease with marked inflammation and fatty infiltration. 31 However, these fibers also had reduced specific force due to myosin loss, which may prohibit compensatory changes in calcium sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…30 Reduced muscle fiber specific force is also found in myotonic dystrophy, a multisystem disorder caused by a repeat expansion of the DMPK gene, and in inclusion body myositis, an inflammatory and degenerative acquired muscle disease. 31,32 In contrast, single muscle fiber specific force in FSHD is intact even in severely affected tissue with marked fatty infiltration. This indicates that muscle weakness in FSHD does not occur through a primary effect of DUX4 on muscle fiber contractility.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 More recent studies have incorporated quantitative MRI techniques, such as muscle fat fraction (FF) and T 2 mapping, 17 with some exploring longitudinal changes. 18 , 19 , 20 , 21 , 22 Because repeated biopsies for monitoring disease progression are unrealistic, quantitative MRI and magnetic resonance spectroscopy (MRS) are now commonly used in many follow‐up studies of neuromuscular diseases to non‐invasively assess both acute and chronic pathological changes. The ultimate goal is to use these objective MRI/S‐based quantitative biomarkers as surrogate outcome measures in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, MRI protocols consist of qualitative T 1 and fat‐suppressed T 2 ‐weighted MRI to evaluate muscle fat replacement, muscle atrophy, and changes in intramuscular water distribution due to active muscle damage, especially inflammation 12–16 . More recent studies have incorporated quantitative MRI techniques, such as muscle fat fraction (FF) and T 2 mapping, 17 with some exploring longitudinal changes 18–22 . Because repeated biopsies for monitoring disease progression are unrealistic, quantitative MRI and magnetic resonance spectroscopy (MRS) are now commonly used in many follow‐up studies of neuromuscular diseases to non‐invasively assess both acute and chronic pathological changes.…”
Section: Introductionmentioning
confidence: 99%